Hubungan Pengawasan Oleh Mahkamah Agung Dengan Komisi Yudisial Terhadap Prilaku Hakim - Agus Iskandar PP. (Universitas Bandar Lampung (UBL), 2014)
With the supervision carried out by the Supreme Court and the Judicial Commission would be very closely related to the independence of judges in deciding a case. As for the problem of this research is how the relationship supervision by the Supreme Court and the judicial commission. Normative juridical approach and empirical using secondary data and primary data. Based on the results, it can be concluded that the supervision is done by the Supreme Court and the Judicial Commission will not result in judges be independent, if the supervision is done it does not exceed the authority regulated by law. It is suggested, should the Supreme Court Monitoring should be effected, and the change of the Judicial Commission Law urgent is done so that the Judicial Commissions role in creating an independent judicial power can be realized.